KONSUMSI PANGAN BERHUBUNGAN DENGAN PENYERAPAN ZAT BESI PADA IBU HAMIL - kurniati dwi utami; Rieska Indah Muliani; Satriani Satriani (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2020)
The prevalence of Anemia during pregnancy has become the worldwide health problem (24,8%). For tackling the iron deficiency anemia is taking care of the consumption of certain nutrients, especially the enhancer and the inhibitor of iron dietary sources. This study was aimed to analyse the relation between the foods consumption and hemoglobin level and the bioavailability of iron dietary sources among pregnant mothers. The method of this study was a cross-sectional study design. The location of the study was Trauma Center and Mangkupalas Public Health Center. In total, 80 respondents participated in this study. Their foods consumption were interviewed using food recall 24 hour and semi-quantitative food frequency questionnaires. Hemoglobin levels of respondents were taken by health workers in each public health center by using standardized cyanmethemoglobin method. Positive correlation was found between fruits consumption and iron dietary bioavailability (r=0,316, p=0,004), while negative correlation also found between vegetable consumption (r= -0,288; p=0,009), other foods consumption (r= -0,253, p=0,024) and hemoglobin levels among pregnant mothers. In this article found that food intake can affect iron dietary bioavailability in pregnant woman Keywords: iron dietary bioavailability ,pregnant mothers, food intake